Search for a Standard Model Higgs boson in the mass range 200-600GeV in the H→ZZ→ℓ+ℓ-qq̄ decay channel with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Acerbi, E; et al. (2012)
A search for a heavy Standard Model Higgs boson decaying via H→ZZ→ℓ+ℓ-qq̄, where ℓ=e or μ, is presented. The search uses a data set of pp collisions at s=7TeV, corresponding to an integrated luminosity of 4.7fb-1 collected in 2011 by the ATLAS detector at the CERN LHC. No significant excess of events above the estimated background is found. Upper limits at 95% confidence level on the production cross section of a Higgs boson with a mass in the range between 200 and 600GeV are derived. A Standard Model Higgs boson with a mass in the range 300GeV≤mH≤322GeV or 353GeV≤mH≤410GeV is excluded at 95% CL. The corresponding expected exclusion range is 351GeV≤mH≤404GeV at 95% CL. © 2012 CERN.